Real life experience of patients with locally advanced gastric and gastroesophageal junction adenocarcinoma treated with neoadjuvant chemotherapy: a Turkish oncology group study - Basoglu, Tugba; Sakin, Abdullah; Erol, Cihan; Ozden, Ercan; cabuk, Devrim; Cilbir, Ebru; Yumuk, Perran Fulden (Taylor & Francis Ltd, 2023)
Neoadjuvant chemotherapy (NACT) in gastroesophageal junction (GEJ) and gastric cancer (GC) was shown to improve survival in recent studies. We aimed to share our real-life experience of patients who received NACT to compare the efficacy and toxicity profile of different chemotherapy regimens in our country. This retrospective multicentre study included locally advanced GC and GEJ cancer patients who received NACT between 2007 and 2021. Relation between CT regimens and pathological evaluation were analysed. A total of 794 patients from 45 oncology centers in Turkey were included. Median age at the time of diagnosis was 60 (range: 18-86). Most frequent NACT regimens used were FLOT (65.4%), DCF (17.4%) and ECF (8.1%), respectively. In the total study group, pathological complete remission (pCR) rate was 7.2%, R0 resection rate 86.4%, and D2 dissection rate was 66.8%. Rate of pCR and near-CR (24%), and R0 resection (84%) were numerically higher in FLOT arm (p > 0.05). Patients who received FLOT had also higher chemotherapy-related toxicity rate compared to patients who received other regimens (p > 0.05). Median follow-up time was 16 months (range: 1-154 months). Estimated median overall survival (OS) was 58.4months (95% CI: 35.2-85.7) and disease-free survival (DFS) was 50.7 months (95% CI: 25.4-75.9). The highest 3-year estimated OS rate was also shown in FLOT arm (68%). We still do not know which NACT regimen is the best choice for daily practice. Clinicians should tailor treatment regimens according to patients' multifactorial status and comorbidities for to obtain best outcomes. Longer follow-up period needs to validate our results.
Keywords: Gastric cancer; gastroesophageal junction cancer; neoadjuvant chemotherapy